2007
DOI: 10.3132/pcrj.2007.00062
|View full text |Cite
|
Sign up to set email alerts
|

Concerns of patients with allergic rhinitis: the Allergic Rhinitis Care Programme in South Africa

Abstract: Background: The major reason for treating chronic rhinitis is to improve quality of life. Although primary symptoms cause morbidity in their own right, these symptoms are significantly aggravated by the impact of cognitive dysfunction and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…175 In addition to upper respiratory symptoms, it is important to determine the effect of rhinitis on QOL, including symptoms of fatigue, sleep disturbances, learning and attention problems, and absenteeism and presenteeism (present but with impaired function) at work and/or school. [176][177][178][179] The psychological ramifications of untreated allergic rhinitis can lead to low self-esteem, shyness, depression, and anxiety. 180 Recent findings that the sexual QOL is affected by seasonal allergic rhinitis and that appropriate treatment improves the patient's sexual functioning emphasizes that allergic rhinitis is an underappreciated disease with systemic effects.…”
Section: Ciliary Dysfunction Syndromes [Summary Statement 34]mentioning
confidence: 99%
See 1 more Smart Citation
“…175 In addition to upper respiratory symptoms, it is important to determine the effect of rhinitis on QOL, including symptoms of fatigue, sleep disturbances, learning and attention problems, and absenteeism and presenteeism (present but with impaired function) at work and/or school. [176][177][178][179] The psychological ramifications of untreated allergic rhinitis can lead to low self-esteem, shyness, depression, and anxiety. 180 Recent findings that the sexual QOL is affected by seasonal allergic rhinitis and that appropriate treatment improves the patient's sexual functioning emphasizes that allergic rhinitis is an underappreciated disease with systemic effects.…”
Section: Ciliary Dysfunction Syndromes [Summary Statement 34]mentioning
confidence: 99%
“…725 Severe allergic rhinitis has been associated with diminished QOL, disordered sleep (in as many as 76% of patients), and impairment in work performance. 10,179,726 Seasonal allergic rhinitis symptoms typically appear during a defined season in which aeroallergens are abundant in the outdoor air. The length of seasonal exposure to these allergens is dependent on geographic location and climactic conditions.…”
Section: Seasonal and Perennial Allergic Rhinitismentioning
confidence: 99%
“…[32][33][34][35][36][37] It grades recommendations into two levels -strong and weak -and quality evidence into four categories -high, moderate, low and very low. 27,28 While the quality of evidence is one of the factors influencing the strength of a recommendation, this strength is also influenced by the balance between the benefits and harms, resource utilisation and patients' views 3 (Tables 1 and 2). The GRADE approach is therefore closer to patients' needs than former grading systems based on RCT results.…”
Section: Evolution Of Concepts In Guideline Developmentmentioning
confidence: 99%
“…1 Although allergic rhinitis is not usually a severe disease, it alters the social life of patients, and affects school performance and work productivity. 2,3 Moreover, the costs incurred by rhinitis are substantial. Asthma and rhinitis are common co-morbidities suggesting the concept of "one airway, one disease".…”
Section: Introductionmentioning
confidence: 99%
“…[12] Many South African studies have suggested that CR impacts significantly on patient quality of life and the major effect is impaired sleep. [13][14][15] Trivialising CR as a minor, non-life-threatening illness promotes the idea that CR does not affect patients significantly.…”
Section: Impact Of Rhinitis On South Africansmentioning
confidence: 99%